II. Morphometry of wings of worker bees of the subspecies Apis mellifera mellifera L. (Polissya population of Zhytomyr region) - Galatyuk, Oleksandr; Yarovets, Volodymyr; Babenko, Volodymyr; Cherevatov , Volodymyr; Gutyj, Bogdan; Grigorenko, Andrii; Strilchuk, Mykhailo; Stolyar, Ihor (ScienceRise: Biological Science, 2023)
The uncontrolled spread of the subspecies A. m. carnica, A. m. ligustica, and A. m. caucasica has led to a reduction in the areas of pure "dark forest bees" populations belonging to the subspecies A. m. mellifera in their natural habitats within Ukraine. Due to the need to use dark forest bees in breeding, it became necessary to identify the locations of individual populations of bees belonging to the A. m. mellifera subspecies. The purpose of the work is to create an accessible and at the same time complete methodology for classifying bee wing phenotypes, which would make it possible to determine the probable breed of worker bees, the type and degree of hybridization of the main breed with impurities, and to identify "purebred" bee families by the wing phenotype suitable for further breeding. Material and methods of research: Using discriminant analysis of data, at the first stage of the study, 1500 wings of bee families were classified using 8 features: Ci, Dbi, Disc.sh, Pci, Ri, Сі.3, Сі.2, Сi.2.1, for which there was preliminary information about the possible belonging of the wing phenotype to the subspecies A. m. mellifera or its hybrids. At the second stage, additional 1212 wings of bee colonies were studied, about which there were doubts about their breed. Results of research and discussion: The wings are reliably divided into four clusters, indicating the presence of four sufficiently distinct groups among the studied wings in terms of phenotype. Conclusions and prospects for further research: A classification model has been created that allows for effective discrimination of the wings of working bees of bee colonies in Ukraine, the subspecies A. m. mellifera. Phenotypic values of indices of four Polissia micro-populations of bees, used as reference standards for possible hybridization detection, have been established, which can serve as standards in future research. Four colonies have been found, whose queens produce bees of the A. m. mellifera type of the Polissia population, and three colonies whose queens produce bees of the A. m. macedonica hybrid and can be used for further selection work